Thottea aroangensis, a new species of Aristolochiaceae from central Vietnam - Le, Tuan Anh; Dinh, Dien; Doan, Quoc Tuan; Nguyen, Quang Hoa Anh; Tagane, Shuichiro (Phytotaxa, 2021)
Thottea aroangensis T.A. Le, D. Dien & Tagane (Aristolochiaceae) is described based on the specimen collected from the A Roang commune, A Luoi district, Thua Thien Hue province, central Vietnam. This species is characterized by subshrub habit 70–90 cm tall, inflorescence at base of stem close to ground level, campanulate and obscurely lobed perianth ca. 2.6 cm long, inside of perianth tube with creamy white patches, and 20 stamens in 2 whorls, by which combination it is clearly distinguished from the other species of Thottea in Vietnam and its surrounding countries. Morphological descriptions, photographs, a distribution map, vernacular name, and preliminary conservation status are provided for T. aroangensis.